PENERAPANPEMBELAJARAN KOOPERATIF CLASSWIDE PEER TUTORING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA SUB POKOK BAHASANOPERASI HITUNGBENTUK ALJABAR KELASVIII D SMP NEGERI 7JEMBERSEMESTER GANJIL TAHUNAJARAN 2013/2014 - Septi, Dwi; Hobri, H (Department of Mathematics Education , University of Jember, 2014)
Abstract: This study aims to determine the application of learning to improve the activity and student learning outcomes in the form of algebraic arithmetic operations. Classwide Peer Tutoring learning requires students to learn to compete but still interact and work together in a fun and familiar attitude of responsibility, this study may affect the students' social and academic personalities. Subjects were students of class VIII D SMP 7 Jember in odd semester of academic year 2013/2014. This study design is Classroom Action Research (CAR), and collection methods using observation, interview, test and documentation of data. The results showed that the activity and learning outcomes has increased. Student activity cycle I was 68.25% and the second cycle was 77.29%. While student learning outcomes first cycle of 66.67%, while the percentage of completeness in the second cycle increased to 90.47%. Thus, this study can enhance the activity and student learning outcomes Key Words: Classwide Peer Tutoring, algebraic arithmetic operations, student’s activity, student’s learning outcomes